Minimum mortality temperature by cause of death and age group: A multi-country observational study (1990–2019) - Seunghyun Eom; Aurelio Tobias; Masahiro Hashizume; Daewon Yang; Claire Demoury; Eric Lavigne; Aleš Urban; Klea Katsouyanni; Francesco Sera; Paul Lester Carlos Chua; Susana das Neves Pereira da Silva; Dominic Royé; et al. (Environmental Research, 2026)

Influence of pillar plants in vegetation patches on soil carbon in hyperarid ecosystems of the AlUla region - Oscar Pascal Malou; Stéphane Boivin; Baptiste Kerfriden; David Sebag; Jérôme Nespoulous; Ines Ben Ammar; Hassan Boukcim; Yassine Fendane; Sami D. Almalki; Shauna K. Rees; Abdalsamad Aldabaa; Ahmed H. Mohamed; et al. (Journal of Arid Environments, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Potential bedrock exposures of Schrödinger impact melt sheet and/or polymict impact breccias within a crater floor fracture system and volcanic vent - David A. Kring; Valentin T. Bickel; Pascal Lee; Amy L. Fagan; Jennifer L. Heldmann; Rick C. Elphic; David J. Lawrence; Timothy J. Parker; Harrison H. Schmitt (Planetary and Space Science, 2025)

Effects of wind turbine dimensions on the collision risk of raptors: A simulation approach based on flight height distributions - Tonio Schaub; Raymond H.G. Klaassen; Caroline De Zutter; Pascal Albert; Olivier Bedotti; Jean-Luc Bourrioux; Ralph Buij; Joël Chadœuf; Celia Grande; Hubertus Illner; Jérôme Isambert; Kjell Janssens; et al. (Science of The Total Environment, 2024)

The impact of cooking methods on the physical, sensory, and nutritional quality of fish - Sook Chin Chew; Yu Hsuan How; Lee Sin Chang; Choon Hui Tan; Kalvin Meng Jun Chuo; Stephenie Yoke Wei Wong; Pascal Degraeve; Kar Lin Nyam (International Journal of Gastronomy and Food Science, 2024)

A comparison between mutational profiles in tumour tissue DNA and circulating tumour DNA in head and neck squamous cell carcinoma – A systematic review - Xiaomin Huang; Paul Leo; Lee Jones; Pascal H.G. Duijf; Gunter Hartel; Lizbeth Kenny; Sarju Vasani; Chamindie Punyadeera (Mutation Research - Reviews in Mutation Research, 2024)

The association of COVID-19 incidence with temperature, humidity, and UV radiation – A global multi-city analysis - Luise Nottmeyer; Ben Armstrong; Rachel Lowe; Sam Abbott; Sophie Meakin; Kathleen M. O'Reilly; Rosa von Borries; Rochelle Schneider; Dominic Royé; Masahiro Hashizume; Mathilde Pascal; Aurelio Tobias; et al. (Science of The Total Environment, 2023)

Smart Sustainable Cities of the New Millennium: Towards Design for Nature - Chiara Catalano; Mihaela Meslec; Jules Boileau; Riccardo Guarino; Isabella Aurich; Nathalie Baumann; Frédéric Chartier; Pascale Dalix; Sophie Deramond; Patrick Laube; Angela Ka Ki Lee; Pascal Ochsner; et al. (Circular Economy and Sustainability, 2021)
Urban environments consist of a mosaic of natural fragments, planned and unintentional habitats hosting both introduced and spontaneous species. The latter group exploits abandoned and degraded urban niches which, in the case of plants, form what is called the third landscape . In the Anthropocene, cities, open spaces and buildings must be planned and designed considering not only human needs but also those of other living organisms. The scientific approach of habitat sharing is defined as reconciliation ecology , whilst the action of implementing the ecosystem services and functioning of such anthropogenic habitats is called Urban Rehabilitation . However, urban development still represents the main cause of biodiversity loss worldwide. Yet, the approach of planners and landscape architects highly diverges from that of ecologists and scientists on how to perceive, define and design urban green and blue infrastructure. For instance, designers focus on the positive impact that nature (generally associated with indoor and outdoor greeneries) has on human well-being, often neglecting ecosystems’ health. Instead, considering the negative impact of any form of development and to achieve the no net loss Aichi’s objectives, conservationists apply mitigation hierarchy policies to avoid or reduce the impact and to offset biodiversity. The rationale of this review paper is to set the fundamentals for a multidisciplinary design framework tackling the issue of biodiversity loss in the urban environment by design for nature . The method focuses on the building/city/landscape scales and is enabled by emerging digital technologies, i.e., geographic information systems, building information modelling, ecological simulation and computational design.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

RGTA® or ReGeneraTing Agents mimic heparan sulfate in regenerative medicine: from concept to curing patients - Denis Barritault; Marie Gilbert-Sirieix; Kim Lee Rice; Fernando Siñeriz; Dulce Papy-Garcia; Christophe Baudouin; Pascal Desgranges; Gilbert Zakine; Jean-Louis Saffar; Johan van Neck (Glycoconjugate Journal, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)